Sugar and Aggressive and Inattentive Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The effect of a sucrose challenge on aggressive behavior and sustained attention in a sample of young hyperactive boys and age-matched control subjects was studied at the Schneider Children's Hospital, Long Island Jewish Medical Center, New York, and Albert Einstein College of Medicine, Bronx, New York.